Doświadczanie czasu w twórczości Idy Fink - Kotarska, Ewelina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The concept of time in Ida Fink’s works functions as a prewar period but mainly as the Holocaust period. It bears traces of three temporal perspectives: the past, the presence, and the future, and therefore it makes the temporal hybrid. The characters in Ida Fink’s books experience the period of the mass murder of Jews as a present period or near future. Their fate is expressed in the future perspective. The period of the Holocaust is a period of death, endless threats and also great changes in terms of the ways the characters of Ida Fink’s books behave and think. Experiencing the period of the mass murder of Jews is varied and depends on the situation they are in. The author presented the multitude of these kinds of situations, she presented the characters’ fate on different temporal planes. As a result she emphasized the complexity of time and the multifaceted of human fates.